Determination of histological and genotoxic parameters of Nile Tilapia, Oreochromis niloticus exposed to lead (Pb): Parameters of fish exposed to lead (Pb) - Maryam, Sadeema; Naz, Huma; Ahmed, Tanveer; Omran, Awatif; Alanazi, Yasmene F.; Usman, Muhammad; Ijaz , Muhammad Umar; Shah, Syed Qaswar Ali; Qazi , Adnan Ahmad; Ali , Basharat; Ali, Habib; Alasmari, Abdulrahman; et al. (Cellular and Molecular Biology, 2023)
This study investigates the hazardous effects of lead on the histological and genotoxic parameters of the fish, Oreochromis niloticus. Present work was conducted in a series of three steps. In first step, acute toxicity, LC50 and lethal lead concentration were measured using Probit analysis method. LC50 value and lethal concentration for O. niloticus was measured as 77.673 mgL-1 and 150.924 mgL-1, respectively. In second step, histological changes were assessed by preparing slides of tissues of the gills, liver and kidney of both control and Pb-stressed O. niloticus and examining the respective tissues under the light microscope. The inferences showed significant histological alterations (p<0.05) in the gills of Pb-exposed fish including necrosis, edema, vascular congestion, shortening and curling and lifting of the epithelium of secondary lamella in gills. The cellular degeneration and dilation of sinusoids in liver and loss of hemopoietic tissue, necrosis and edema in kidney was observed. Histomorphometry of the liver showed a decrease in diameter of the central vein and hepatocyte along with an increase in width of sinusoids. The histomorphometry of kidney showed an increase in the diameter of renal corpuscle, glomerulus, proximal and distal convoluted tubules. The nuclear anomalies were studied in the RBCs of fish. Non-parametric Mann-Whitney U-test was conducted to compare nuclear abnormalities and the frequency of micronuclei among the control and lead-treated fish groups. Results declared an increased micronucleus, notched and de-shaped nuclei frequency, in RBCs of fish exposed to lead as compared to control group.